Isolation, characterization, and validation of RP-HPLC method for the quantification of quercetin in Huberantha senjiana leaf extract - Rajakannu Pandiyan, Kaliappan Ilango& (Journal of Applied Pharmaceutical Science, 2020)
Huberantha senjiana (Annonaceae) - an endemic tree of Pakkamalai Reserve Forest Gingee Hills, Tamil Nadu, India was subjected to preliminary phytochemical tests and high-performance liquid chromatography (HPLC) fingerprint chromatogram was established for use in future research. Subsequently, the HPLC-DAD-ESI (+) MS analysis to identify the common biomarkers revealed the presence of Quercetin, a polyphenolic flavonol in the ethyl acetate extract of the leaves. An isocratic reversed-phase (RP)-HPLC method for the quantification of quercetin was developed with phenomenex, RP C18 column using mobile phase [(H2O (0.1% formic acid, A); (MeOH: ACN, (40:15v/v), B), 40:60 (v/v)] with a flow rate of 0.8 ml/min, detection max at 254 nm with a retention time of 7.58 minutes and was validated according to the International Conference on Harmonization Q2B guidelines. Linearity was achieved with the concentration range of 5.0–17.5 μg/ml with a R2 value of 0.996. Sensitivity was demonstrated with the limit of detection of 2.28 μg/ml and the limit of quantification of 6.92 μg/ml. The robustness was estimated from purposeful changes in the composition of the mobile phase, wavelength, and flow rate and the limits were Not More Than (NMT) 4%. The foliar concentration of quercetin was found to be 0.0055% w/w. The structural confirmation was done by the isolation and characterization by the divergent spectral analysis. This is the first published report on the identification, quantification, and isolation of quercetin in the leaves of H. senjiana species.
Keywords: Huberantha senjiana, high-performance liquid chromatography, HPLC fingerprints, isolation; quercetin.